1982
DOI: 10.1017/s0043174500040947
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sweetcorn (Zea mays) to Alachlor, EPTC + R-25788, and Vernolate + R-25788

Abstract: Alachlor [2-chloro-2′,6′-diethyl-N-(methoxymethyl)acetanilide] at 6.7 kg/ha, twice the recommended rate, stunted early-season growth of ‘Jubilee,’ ‘Commander,’ and 'Stylepak’ sweetcorn (Zea maysL.) 9 to 15%, reduced plant populations of Commander and Stylepak 12 to 15%, reduced the kernel yield of Jubilee and Stylepak 14 to 16%, and delayed ripening of Jubilee and Stylepak by 2 or 3 days. Alachlor at 3.4 kg/ha slowed early-season growth of Jubilee and Stylepak, but reduced yield and delayed ripening of only Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Alachlor, metolachlor, butylate plus dichlormid, and EPTC plus dichlormid are the primary herbicides used for selective weed control in sweet com. Several re searchers (2,7,9) have reported that alachlor, EPTC plus dichlormid, vemolate (5-propyl dipropylcarbamothioate) plus dichlormid, and metolachlor have reduced early seedling growth of several sweet com cultivars. Growth reductions of sweet com seedlings (Zea mays L. 'NK-199') exposed to metolachlor using nutrient culture techniques have been reported also (5).…”
Section: Introductionmentioning
confidence: 99%
“…Alachlor, metolachlor, butylate plus dichlormid, and EPTC plus dichlormid are the primary herbicides used for selective weed control in sweet com. Several re searchers (2,7,9) have reported that alachlor, EPTC plus dichlormid, vemolate (5-propyl dipropylcarbamothioate) plus dichlormid, and metolachlor have reduced early seedling growth of several sweet com cultivars. Growth reductions of sweet com seedlings (Zea mays L. 'NK-199') exposed to metolachlor using nutrient culture techniques have been reported also (5).…”
Section: Introductionmentioning
confidence: 99%